Siti Akila Enterprise / Muhammad Azrul Naim Azhar, Noorfarah Lyana Amran, Nurul Jannah Mustaza, Siti Najwa Sulaiman, Nurfakhira Atiqah Abdul Karim and Nur Athira Ahmad Sarudin - Azhar, Muhammad Azrul Naim; Amran, Noorfarah Lyana; Mustaza, Nurul Jannah; Sulaiman, Siti Najwa; Abdul Karim, Nurfakhira Atiqah; Ahmad Sarudin, Nur Athira (2019)
SITI AKILA ENTERPRISE was established on 2004. The company belongs to Encik Abdul Halim Bin Mokhtar. The company was started small and operated by family members in 2004. At the age of 30, his uncle offers him to help in his bakery in terms of the development skills. After 3 years operation, he got an offer from RISDA and obtained loan from MARA The company is operated in TL 72 Kampung Parit Raja Idris, Bukit Gambir, Johor.